Is Productive Zakat Effective as an Economic Catalyst for Village Farmers? - Okyviandi Putra Erlangga,; Muhammad Nafik Hadi Ryandono, (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
This study aims to find out how the role of productive zakat through empowerment carried out by LAZ Dompet Dhuafa on improving the welfare of farmers in Kwajon Village, Ponorogo Regency, East Java. This study uses a descriptive qualitative research approach with a case study method. The data collection process was conducted through an interview method with 13 informants from which there were 11 mustahiq, 1 program assistant and 1 village head. The results of the study show that the distribution of productive zakat through farmer empowerment programs has a positive role in improving farmers' welfare. This can be seen through the increase in income obtained by farmers.